DEDUCTIVE AND INDUCTIVE INSTRUCTIONS FOR TEACHING ENGLISH GRAMMAR IN ONLINE CLASSROOM - Eli Indriyani, Christina (Lire Journal (Journal of Linguistics and Literature), 2021)
Realizing the importance of teaching grammar to young learners, pre service teachers, as prospective teachers, need to reflect their own grammar teaching performance. Moreover, during the covid-19 pandemic outbreak where all learning processes are conducted online, teaching strategy needs to be considered. Therefore, this study aimed to find out whether the pre-service teachers apply the deductive or inductive teaching instructions in teaching grammar to young learners during the online class and to investigate how pre-service teachers develop the instructions. To reach the objectives, qualitative research was employed by observing and analysing the teaching videos of thirteen pre service teachers. The pre service teachers were the students of English Education Department in a private university in Jakarta who enrolled the Teaching Internship program. All videos were transcribed and then the analysed data were put in a table and coded to ease the identification of deductive and inductive instructions. The results revealed that more students adopted deductive grammar instructions in teaching grammar for young learners rather than inductive instruction. Furthermore, the way the pre service teachers developed both instructions followed the PPP and TTT models with different emphasis on the Presentation and Teach parts. The tendency done in the Presentation part for inductive teaching was the pre service teacher acted as instructor whereas the Teach part in inductive teaching was as facilitator. Eventually, from this study it can be concluded that pre service teachers adopted deductive and inductive grammar instructions because both are suitable for teaching grammar to young learners in online classroom setting within consideration of meaningful learning activities.